Terminal Complement Blockade after Hematopoietic Stem Cell Transplantation Is Safe without Meningococcal Vaccination - Jodele, Sonata (Biol Blood Marrow Transplant, 2016)
Eculizumab inhibits terminal complement-mediated intravascular hemolysis in patients with paroxysmal nocturnal hemoglobinuria and complement-mediated thrombotic microangiopathy (TMA) in patients with atypical hemolytic uremic syndrome and is now used as a first-line therapy in these diseases. Eculizumab is available only through a restricted program under a Risk Evaluation and Mitigation Strategy (REMS) because of an increased risk of meningococcal infections in persons without adequate functional complement. Administration of meningococcal vaccine is required at least 2 weeks before administering the first dose of eculizumab, and this advice is included in the product label. Eculizumab use for treatment of TMA in hematopoietic stem cell transplantation (HSCT) recipients brings a significant dilemma regarding REMS required meningococcal vaccination. TMA after HSCT usually occurs within the first 100 days after transplantation when patients are severely immunocompromised and are not able to mount a response to vaccines. We evaluated 30 HSCT recipients treated with eculizumab for high-risk TMA without meningococcal vaccine. All patients received antimicrobial prophylaxis adequate for Neisseria meningitides during eculizumab therapy and for 8 weeks after discontinuation of the drug. Median time to TMA diagnosis was 28 days after transplant (range, 13.8 to 48.5). Study subjects received a median of 14 eculizumab doses (range, 2 to 38 doses) for HSCT-associated TMA therapy. There were no incidences of meningococcal infections. The incidences of bacterial and fungal bloodstream infections were similar in patients treated with eculizumab (n = 30) as compared with those with HSCT-associated TMA who did not receive any complement blocking therapy (n = 39). Our data indicate that terminal complement blockade in the early post-transplant period can be performed without meningococcal vaccination while using appropriate antimicrobial prophylaxis until complement function is restored after therapy completion.